Treatment outcomes of dogs with transitional cell carcinoma - Chu, Ka To; Nekouei, Omid; Giuliano, Antonio (Frontiers in Veterinary Science, 2025)
Transitional cell carcinoma (TCC) is the most prevalent cancer of the urinary tract in dogs. The prognosis is often poor, and the optimal standard treatment has not been established. The objectives of this study were to (1) describe the clinical outcomes of dogs with TCC, and (2) determine the potential effects of tumor locations and treatment modalities on the survival times of patients. Electronic records of client-owned dogs with TCC treated with different modalities in a large veterinary hospital in Hong Kong (2005–2024) were evaluated. Of 84 confirmed cases included in the study, 49 (58.3%) died or were euthanized due to TCC. Tumors were located in the bladder neck or trigone region (41), apex (26), prostate (10), and urethra (7). Metastases were detected in 10 patients (12%) at diagnosis, including 4 peripheral lymph nodes, 4 lungs, and 2 in the lumbar spine. Of 84 cases, 4 (4.8%) did not receive any treatments, 14 (16.7%) underwent surgery, 25 (29.7%) received metronomic chemotherapy with chlorambucil with/without methotrexate, 27 (32.1%) received COX-2 inhibitors alone, and 14 (16.7%) received conventional chemotherapy, of which, 5 were later switched to metronomic chemotherapy. The overall median survival time was 233 days. There was no statistically significant difference in patients’ survival between tumor locations (p > 0.05), aside from tumors involving the prostate that had the shortest MST (88 days). Metronomic chemotherapy led to a significantly longer survival time (median of 303 days) than the other treatment groups (p < 0.05), with the lowest incidence of adverse events. Metronomic chemotherapy using chlorambucil was well-tolerated and can be considered as a single modality treatment or as adjunctive therapy to conventional chemotherapy in dogs with TCC.